Evaluation of Islam education teachers training implementation - Helen Sabera Adib; Djemari Mardapi; Zamroni Zamroni; Adam Jait (Jurnal Penelitian dan Evaluasi Pendidikan, 2019)
The purpose of this study is to evaluate the implementation of the Islam education teachers' training in the Religion Education and Training Center in Palembang. This study is an evaluation research conducted using the Islam Education Teachers Training model, which consists of Context, Input, Process, and Product aspects. Sources of information in this study include the training organizers, Widyaiswara (civil servants assigned as instructors), and the participants of the training. Data collection was conducted using questionnaires, observation, and documentation. The data analysis technique used in this study was quantitative descriptive. The results of the study conclude that the implementation of the Islam Education teachers' training program is very successful, as shown by the success indicators in terms of context, input, process, and product aspects.